2018
DOI: 10.1161/hypertensionaha.118.11975
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Phenotype of Elevated Blood Pressure Differs Markedly Between Young Males and Females

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 28 publications
4
25
0
1
Order By: Relevance
“…Although ongoing studies for young adults are currently being investigated, most are still at the initial stages and the long term impact on cardiovascular end points remains to be determined. 56 57 58 Therefore, the insights provided in our study could help to refine strategies for primary prevention and might have important implications for future research.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although ongoing studies for young adults are currently being investigated, most are still at the initial stages and the long term impact on cardiovascular end points remains to be determined. 56 57 58 Therefore, the insights provided in our study could help to refine strategies for primary prevention and might have important implications for future research.…”
Section: Discussionmentioning
confidence: 89%
“…Without a defined association between high blood pressure and cardiovascular risks, developing and implementing standardised treatment advice and guidelines that include young adults is challenging. Although ongoing studies for young adults are currently being investigated, most are still at the initial stages and the long term impact on cardiovascular end points remains to be determined 565758. Therefore, the insights provided in our study could help to refine strategies for primary prevention and might have important implications for future research.…”
Section: Discussionmentioning
confidence: 90%
“…In most studies increased CO has been positively associated with elevated BP [ 16 , 24 , 28 ]. There are also some data supporting gender differences in the contribution of increased cardiac output to hypertension; an analysis from the ENIGMA cohort in young adults showed that males with hypertension tended towards a ‘cardiac’ phenotype, with elevated HR, SV and CO [ 29 ]. Females on the other hand tended towards increased SVR and pulse wave velocity (PWV, a measure of arterial stiffness) described as a ‘vascular’ phenotype.…”
Section: Determinants Of the Static Component Of Bpmentioning
confidence: 99%
“…Определение уровня жесткости сосудистой стенки по величине Alp% для оценки прогноза больных АГ проводилось в работах как отечественных [7,13], так и зарубежных авторов [15][16][17]. В настоящем исследовании были выявлены прямые корреляции Alp% со степенью атеросклеротического поражения сосудов: количеством АСБ, толщиной КИМ.…”
Section: Discussionunclassified